Crisis from Afar. Media Conceptualisations of Events in Brazil after the 2022 Presidential Election - Grzelka, Monika; Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The proximity (localness) of the reported events is closely correlated with their relevance to the audience of media reports—and so the fact that it may be “our business”, that the thing may also affect us, becomes crucial to the decision to deal with the topic in question, but also to the way in which it is dealt with. In this article, we are interested in media conceptualisations of a crisis that is far away, that is “alien”, “foreign”, and thus cannot be narrated through reference to social and receptive experience. We look at the ways in which the exoticisation of distant places and events can be reduced, and thus at strategies for convincing the Polish audience that these are issues that are relevant and worthy of attention. We will look at whether the divisive, deeply political fractures in media narratives also apply to the storytelling about events on the other hemisphere, and whether the ideological filters common in Polish media are also imposed on what is unknown.